STUDY INFLUENCE PERFORMANCE OF AC-BC USING OF VOLCANIC ASH FROM MOUNT SINABUNG AS FILLER IN HOTMIX ASPHALT AND CUTBACK ASPHALT (MC-250) PROCESS - REZA A. MAHA (NIM : 269 15 306), MUHAMMAD
The experimental of volcanic ash as filler, will be used as a mixture of asphalt in pavement to produce a good combination of coarse aggregate, fine aggregate, asphalt and filler. Based on the standard of hot mix asphalt in Indonesia, mixed performance is obtained from Marshall test, Marshall Immersion test, Resilient Modulus test UMATTA, and Fatigue testing with controlling of stress. Meanwhile, the cold mix asphalt performance was obtained from Marshall testing and Marshall immersion testing using MC-250 cutback asphalt, which is combination between a asphalt pen.60/70 with kerosene. HMA and Cutback Asphalt could be do if to get a KAO value from filler of fly ash (standard). Cement ash is also tested the performance of HMA and Cutback Asphalt as a comparison result for Volcanic ash as filler. The mixed performance of HMA Marshall test gives the highest Marshall Stability achieved by volcanic ash filler of Sinabung Mountain with 1453 kg. The results of Marshall immersion testing achieved by cement ash filler gave the highest value of 94.24%. For Cutback Asphalt the highest stability value is achieved by a volcanic ash filler with 640 kg. The results of Marshall immersion testing achieved by cement ash filler gave the highest value of 81.03%. For the Resilient Modulus test results on the volcanic ash mixture of Mount Sinabung gave a value of 5282 MPa at 25°C, and 652 MPa at 45°C, which is the highest value than the cement filler mixer. For the Fatigue test results on HMA with cement ash filler give 94320 cycles value at stress level 1400 Kpa, 68590 cycles at stress level 1276 Kpa, and 45260 cycles at stress level 1199 Kpa, which is the highest value than the volcanic ash of Mount Sinabung. Generally, seen from Bina Marga specification (IKS at least 90%) the test results show that the using of volcanic ash filler for Hot mix asphalt AC-BC, is more durable. But no more stiffness (stiffness) than filler cement ash. For the test results against the cutback asphalt MC-250, That the using of volcanic ash filler has been able to increase the stability value determined by Asphalt Institute MS-14 with Minimum stability value 500 kg and the Marshall residual strength (IKS) value of at least 75%.